Calculations of gaseous and particulate emissions from German agriculture 1990-2016: Report on methods and data (RMD) Submission 2018; Berechnung von gas- und partikelförmigen Emissionen aus der deutschen Landwirtschaft 1990-2016: Report zu Methoden und Daten (RMD) Berichterstattung 2018 - Hans-Dieter Haenel; Claus Rösemann; Ulrich Dämmgen; Ulrike Döring; Sebastian Wulf; Brigitte Eurich-Menden; Annette Freibauer; Helmut Döhler; Carsten Schreiner; Bernhard Osterburg (Johann Heinrich von Thünen-Institut, 2018)
The report at hand (including a comprehensive annex of data) serves as additional document to the National Inventory Report (NIR) on the German green house gas emissions and the Informative Inventory Report (IIR) on the German emissions of air pollutants (especially ammonia). The report documents the calculation methods used in the German agricultural inventory model GAS-EM as well as input data, emission results and uncertainties of the emission reporting submission 2018 for the years 1990 - 2016. In this context the sector Agriculture comprises the emissions from animal husbandry, the use of agricultural soils and anaerobic digestion of energy crops. As required by the guidelines, emissions from activities preceding agriculture, from the use of energy and from land use change are reported elsewhere in the national inventories. [...] – – Der vorliegende Berichtsband einschließlich des umfangreichen Datenanhangs dient als Begleitdokument zum National Inventory Report (NIR) über die deutschen Treibhausgas-Emissionen sowie zum Informative Inventory Report (IIR) über die deutschen Schadstoffemissionen (insbesondere Ammoniak). Der Bericht dokumentiert die im deutschen landwirtschaftlichem Inventarmodell GAS-EM integrierten Berechnungsverfahren sowie die Eingangsdaten, Emissionsergebnisse und Unsicherheiten der Berichterstattung 2018 für die Jahre 1990 bis 2016. Der Bereich Landwirtschaft umfasst dabei die Emissionen aus der Tierhaltung und der Nutzung landwirtschaftlicher Böden sowie aus der Vergärung von Energiepflanzen. Emissionen aus dem Vorleistungsbereich, aus der Nutzung von Energie sowie Landnutzungsänderungen werden den Regelwerken entsprechend an anderer Stelle in den nationalen Inventaren berichtet. [...]
urn:nbn:de:gbv:253-201803-dn059722-0
Keywords: 630; emission inventory; agriculture; animal husbandry; agricultural soils; anaerobic digestion; energy crops; renewable primary products; greenhouse gases; air pollutants; methane; loughing gas; ammonia; particulate matter; Emissionsinventar; Landwirtschaft; Tierhaltung; landwirtschaftliche Böden; anaerobe Vergärung; Energiepflanzen; nachwachsende Rohstoffe; Treibhausgase; Luftschadstoffe; Methan; Lachgas; Ammoniak; luftgetragene Partikel